Giant star-forming regions in interacting galaxies - Firpo, Verónica (2016)
The most violent processes of star formation can be found in interacting galaxies, where gas compression can trigger the formation of giant star-forming regions. Using high-resolution spectroscopic information from MIKE/Magellan and multi- slit data from GM OS/Gemini-South, we propose to improve our knowledge in the chemodynamics of extragalactic star-forming regions. The current analysis is based on a sample of st ar-forming regions located in strongly interacting galaxies. A detailed study of the ionized gaseous component in these regions reveals a complex internal kinematics, which can be identified by asymmetric line profiles and multiple components. The kinematic information suggests that these st ar-forming objects correspond to giant complexes. Future estimations of physical properties such as the electron densities, temperatures and chemical abundances of the different kinematical components will allow us to determine the chemodynamical state of these star-forming objects. This information will be extremely useful to understand the evolution of these systems in interacting galaxies.